2022
DOI: 10.1039/d2cp04338f
|View full text |Cite
|
Sign up to set email alerts
|

The metal dependence of single-metal mediated phosphodiester bond cleavage: a QM/MM study of a multifaceted human enzyme

Abstract: Nucleases catalyze the cleavage of phosphodiester bonds in nucleic acids using a range of metal cofactors. Although it is well accepted that many nucleases rely on two metal ions, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…50 Furthermore, QM calculations on APE1 revealed that indirect metal−substrate ligation is preferred over the direct substrate ligation observed in the crystal structure of the PC (PDB ID: 4IEM, Figure 3a), while QM/MM calculations verified that this metal binding architecture can facilitate the phosphodiester bond hydrolysis in a manner consistent with experimental data. 56,69 A similar water-mediated interaction between Mg 2+ and a nonbridging phosphate oxygen has been detected in the active site of the RC analogue of one-metal-dependent Vvn (PDB ID: 1OUP, Figure 3h). 41 Based on this literature, indirect metal−substrate coordination was investigated for EndoV using MD simulations, in which the octahedral coordination geometry of Mg 2+ was satisfied by D43, D110, and four active site water molecules (Figures S11b, S12b, and Table S2).…”
Section: Direct Metal Coordination To the Nonbridging Oxygen And Indi...mentioning
confidence: 55%
See 4 more Smart Citations
“…50 Furthermore, QM calculations on APE1 revealed that indirect metal−substrate ligation is preferred over the direct substrate ligation observed in the crystal structure of the PC (PDB ID: 4IEM, Figure 3a), while QM/MM calculations verified that this metal binding architecture can facilitate the phosphodiester bond hydrolysis in a manner consistent with experimental data. 56,69 A similar water-mediated interaction between Mg 2+ and a nonbridging phosphate oxygen has been detected in the active site of the RC analogue of one-metal-dependent Vvn (PDB ID: 1OUP, Figure 3h). 41 Based on this literature, indirect metal−substrate coordination was investigated for EndoV using MD simulations, in which the octahedral coordination geometry of Mg 2+ was satisfied by D43, D110, and four active site water molecules (Figures S11b, S12b, and Table S2).…”
Section: Direct Metal Coordination To the Nonbridging Oxygen And Indi...mentioning
confidence: 55%
“…Although no catalytically feasible pathway could be characterized in the present work that involves direct metal coordination to the substrate, an active site configuration involving indirect metal coordination to the substrate has been observed in the endonuclease literature. ,,, Specifically, a crystal structure of a phosphorothioate RC analogue of one-metal-mediated APE1 shows a Mn 2+ -coordinated water within hydrogen-bonding distance to a nonbridging oxygen of the scissile phosphate (PDB ID: 5DG0, Figure b) . Furthermore, QM calculations on APE1 revealed that indirect metal–substrate ligation is preferred over the direct substrate ligation observed in the crystal structure of the PC (PDB ID: 4IEM, Figure a), while QM/MM calculations verified that this metal binding architecture can facilitate the phosphodiester bond hydrolysis in a manner consistent with experimental data. , A similar water-mediated interaction between Mg 2+ and a nonbridging phosphate oxygen has been detected in the active site of the RC analogue of one-metal-dependent Vvn (PDB ID: 1OUP, Figure h) . Based on this literature, indirect metal–substrate coordination was investigated for EndoV using MD simulations, in which the octahedral coordination geometry of Mg 2+ was satisfied by D43, D110, and four active site water molecules (Figures S11b, S12b, and Table S2).…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations